Seismic resilience assessment of corroded reinforced concrete structures designed to the Chinese codes - Yu, Xiaohui (2022)
The natural landscape in China exposes many existing RC buildings to aggressive environments. Such exposure can lead to deterioration in structural performance with regard to resisting events such as earthquakes. Corrosion of embedded reinforcement is one of the most common mechanisms by which such structural degradation occurs. There has been increasing attention in recent years toward seismic resilience in communities and their constituent construction; however, to date, studies have neglected the effect of natural aging. This study aims to examine the effect of reinforcement corrosion on the seismic resilience of RC frames that are designed according to Chinese seismic design codes. A total of twenty RC frames are used to represent design and construction that is typical of coastal China, with consideration given to various seismic fortification levels and elevation arrangements. Seismic fragility relationships are developed for case frames under varying levels of reinforcement corrosion, i.e., corrosion rates are increased from 5% to 15%. Subsequently, the seismic resilience levels of uncorroded and corroded RC frames are compared using a normalized loss factor. It was found that the loss of resilience of the corroded frames is greater than that of their uncorroded counterparts. At the Rare Earthquake hazard level, the corrosion-induced increase in loss of resilience can be more than 200%, showing the significant effect of reinforcement corrosion on structural resilience under the influence of earthquakes.